Terpenos naturais como candidatos ao tratamento da infecção causada pelo Sars-cov-2: estudo in silico da complexação com proteínas virais - Gondim, Natália Chaves (2022)
Coronavirus 2 (SARS-CoV-2) is the virus responsible for COVID-19, a pandemic that has been harming world health since 2020. As there are no approved drugs to prevent or treat COVID-19, this work aims to investigate four terpenes with antiviral potential, seeking complexation with viral capsid proteins. The candidate molecules showed good results in preliminary tests, demonstrating compatibility with specific domains of two viral capsid proteins: “spike glycoprotein” and “main protease”. Computational molecular docking tools with affordable computational cost were used and the fittings were performed by exploring the entire surface of the two target proteins of SARS- CoV-2. Computer simulation of docking by molecular docking investigated chemical compatibility, energetic parameters and chemical bonds to suggest mechanisms of action of terpenes against the binding sites of SARS-CoV-2 structural proteins. The analysis of the complexes formed was performed using the imaging software PyMol 1.4.7. With spike protein, terpenes promoted bonds from 1.8 to 4.2 angstroms, recruiting 4 to 6 amino acid residues, while in Mpro protein, terpenes established bonds from 2.0 to 3.8 angstroms, recruiting 3 to 5 amino acid residues. The best complexes formed were analyzed and compared, seeking to promote the molecular bases that justify the antiviral activity against SARS-CoV-2 and that this activity has its mechanisms elucidated. The theme of this research is of great social and medical- scientific relevance, since the Unified Health System (SUS) urgently needs a panel of antiviral molecules, so that they can be clinically tested and safely implemented, strengthening the therapeutic arsenal that will help in reducing the number of deaths.